The trend of changes in the structure of the regional branch of the regions and their characteristics . (Journal of Economic Research & Business Administration, 2015)
Article territorial and sectoral analysis of the structure of the Republic of Kazakhstan regions , based on an assessment of regional competitive advantages and competitive qabilet- regions of KazakhstanLanguage discussed in the context of their comprehensive study of the socio - economic development.
Keywords: Territorial industry